1993
DOI: 10.1111/j.1559-1816.1993.tb01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer Input and Revised Judgment: Exploring the Effects of (Un) Biased Confidence1

Abstract: An experiment was conducted to test the effects of biased versus unbiased peer input on the revised judgments of others. After completing a set of knowledge items and assessing their confidence in each answer, subjects were: (a) given written input (in the form of answers and confidence assessments) from a peer who had completed the same set of items, and (b) allowed to revise their earlier answers and confidence assessments. Peer input was either overconfident, underconfident, or appropriately confident. Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Our study highlights a new way in which confidence actively shapes our behavior, adding to a growing literature showing how confidence actually affects individual or collective decisions. Previous research showed how when agents interact, the confidence with which advice is expressed affects the use of this information by others (Paese & Kinnaly, 1993; Zalesny, 1990; Zarnoth & Sniezek, 1997) and how well the group will perform (Massoni & Roux, 2017). At the individual level, confidence may serve as a teaching signal when feedback is unavailable (Daniel & Pollmann, 2012; Guggenmos, Wilbertz, Hebart, & Sterzer, 2016; Hainguerlot, Vergnaud, & de Gardelle, 2018; Zylberberg, Wolpert, & Shadlen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights a new way in which confidence actively shapes our behavior, adding to a growing literature showing how confidence actually affects individual or collective decisions. Previous research showed how when agents interact, the confidence with which advice is expressed affects the use of this information by others (Paese & Kinnaly, 1993; Zalesny, 1990; Zarnoth & Sniezek, 1997) and how well the group will perform (Massoni & Roux, 2017). At the individual level, confidence may serve as a teaching signal when feedback is unavailable (Daniel & Pollmann, 2012; Guggenmos, Wilbertz, Hebart, & Sterzer, 2016; Hainguerlot, Vergnaud, & de Gardelle, 2018; Zylberberg, Wolpert, & Shadlen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Groups accord lower social status to individuals who hinder the group's success (e.g., Blau, 1964;Ridgeway & Diekema, 1989). Groups might thus penalize overconfident individuals because overconfidence jeopardizes task performance (Barber & Odean, 2000;Klein & Kunda, 1994;Metcalfe, 1998;Paese & Kinnaly, 1993;Vancouver, Thompson, Tischner, & Putka, 2002).…”
Section: The Case For Punitivenessmentioning
confidence: 99%
“…In a related field, researchers such as Paese and Kinnaly (1993) and Price and Stone (2004) have used numbers to represent the speaker's estimate of the probability of their chosen answer being correct. In the field of probability communication, which bears strong similarities to the area of confidence communication, the mapping of quantitative terms to qualitative terms has established the numerical values placed on different verbal expressions of probability (see Druzdzel, 1989;Clark, 1990, for reviews).…”
mentioning
confidence: 99%